The Influence of Tourism Towards the Dynamics of Women’s Rights in Marriage Law in Bali - ., Ariani; ., Sukerti (Udayana Journal of Social Sciences and Humanities, 2018)
This research aims to examine the influence of tourism on women rights towards the dynamics in marriage law in Bali by answering the questions: 1) How does tourism affect women empowerment, especially in marriage life; 2) By women participation in public sector of tourism, does it create the dynamics of women rights in marriage law in Bali? The method used in this research is empirical law research by interview method to informants and respondents with interview method, analysis data applied qualitatively. The research results showed that tourism has affected on women empowerment. Women can fill job opportunities and business opportunities in the tourism sector either as worker, as independent entrepreneurs or as workers/ entrepreneurs to help their husbands. Oftentimes, women in research villages do multiple livelihood patterns. Women have their own income to increase their personal resources and sustain the familyeconomy, women are not dependent on men as stereotype that have been existed. Tourism also has a real significant effect on women rights dynamics, where women as workers, independent entrepreneurs, workers/entrepreneurs to help their husbands have authority to manage business by autocratic and syncretic decision making pattern which is indicating that women are participating, has rights in decision making.